The effect of social responsibility disclosure on financial performance in the COVID-19 pandemic era - Ika Prayanthi; Novi Swandari Budiarso (Cogent Business & Management, 2022)
This study aims to identify the mediating role of the management accounting information system (MAIS) in the relationship between innovation strategy and the financial performance of industrial companies in Jordan. To achieve the objectives of the study, the prepared a questionnaire, where the number of questionnaires was distributed (374) randomly. Where (358) questionnaires were retrieved by (95.7%) of the total questionnaires sent electronically, and they were distributed to (the general manager, financial manager, chief accountant, internal auditors, and accountants. The study reached several results, most notably: There is no significant mediating role of MAIS on the relationship between management's value orientation towards innovation and financial performance in Jordanian industrial companies. Moreover, there is a significant mediating role of MAIS in the relationship between riskiness and financial performance in Jordanian industrial companies. In view of these results, the study recommends to the Jordanian industrial companies' management the importance of applying the modern MAIS because it has become a critical component, and it is difficult to achieve a competitive advantage and stay in the market without relying on systems.Various researchers have been conducted, and the results are mixed, inconsistent, and conducted before era of pandemic. The purpose of this study is to examine the impact of corporate social responsibility disclosure on financial performance in the era of pandemic base on Indonesian context. We use quantitative method using regression analysis. Secondary data have been collected for 36 companies in consumption industry listed in Indonesian Stock Exchange for the period of 2019-2021 which are the challenging years. We measure the disclosure of social responsibility using the global reporting index in the company's annual report. For financial performance variables, we use return on asset, return on equity and Tobin's Q, to see the consistency of the result. For the control variables, we use leverage and total asset. We found that corporate social responsibility disclosure consistently has a significant positive effect on return on asset, return on equity and for the value of Tobin's Q. The corporate social responsibility in this study is assessed using personal judgment based on the Global Reporting Initiative social responsibility disclosure indicators. This proves that especially in the era of pandemic, non-financial information like corporate social responsibility disclosure is very powerful for the succeed of the company in the case of Indonesian context. This research was conducted using period when the company faced crisis that was different from previous economic crisis. Another consideration is about global pressure related to the issue of the impact of climate change. The result of this study will contribute to whether there is consistency in the findings when tested during pandemic crisis compared to the economic situation before pandemic.
Keywords: 650; corporate social responsibility; financial performance; pandemic